Beyond TiO2: Cerium‐Doped Zinc Oxide as a New Photocatalyst for the Photodegradation of Persistent Pollutants. Issue 12 (12th August 2016) - Paganini, Maria Cristina; Dalmasso, Daniele; Gionco, Chiara; Polliotto, Valeria; Mantilleri, Lorenzo; Calza, Paola
Abstract: We prepared via hydrothermal synthesis zinc oxide samples doped with cerium. The samples were characterized via powder X Ray Diffraction measurements, Diffuse Reflectance UV Vis spectroscopy, Scanning Electron Microscopy and Transmission Electron Microscopy with EDX (Energy Dispersive X‐Ray spectroscopy) analysis, and BET (Brunauer–Emmett–Teller) surface area analysis. XRD measurements reveal the formation of highly crystalline materials; wurtzite is the most important. All materials were tested using phenol as model molecule and their performances were compared with TiO2 P25. The material showing the best performance, namely Ce‐doped ZnO, was then used to abate some emerging pollutants. We chose three iodinated X‐ray contrast agent (ICM), iopromide, iopamidol and diatrizoate, known to be recalcitrant to traditional advanced oxidation processes. In the presence of TiO2 P25, all ICM exhibited a slow degradation, with t1/2 ranging from 30 min (iopamidol) to 120 min (diatrizoate) and several hours are required for their complete disappearance. The employment of Ce‐doped ZnO leads to a sharp increase in their disappearance, with t1/2 obtained within 15 min (iopamidol) or 25 min (diatrizoate) and the complete abatement is achieved within 2 h. Abstract : In this paper a photocatalyst based on Ce doped Zinc Oxide has been synthesized, characterized and tested in the abatement of phenol and some recalcitrant pollutants (Iopamidol, iopromide and diatrizoate). It is more efficient than the benchmark titania P25.